Liraglutide-Induced Weight Loss May be Affected by Autonomic Regulation in Type 1 Diabetes - Hansen, Christian Stevns; Frandsen, Christian Seerup; Fleischer, Jesper; Vistisen, Dorte; Holst, Jens Juul; Tarnow, Lise; Knop, Filip Krag; Madsbad, Sten; Andersen, Henrik Ullits; Dejgaard, Thomas Fremming (Frontiers in Endocrinology, 2019)
The role of the autonomic nervous system in the efficacy of glucagon-like peptide-1 receptor agonists (GLP-1 RA) in patients with type 1 diabetes is unknown. We assessed the association between autonomic function and weight loss induced by the GLP-1 RA liraglutide. Methods Lira-1 was a randomised, double-blind, placebo-controlled trial assessing the efficacy and safety of 1.8 mg liraglutide once-daily for 24 weeks in overweight patients with type 1 diabetes. Autonomic function was assessed by heart rate response to deep breathing (E/I ratio), to standing (30/15 ratio), to the Valsalva manoeuvre and resting heart rate variability (HRV) indices. Associations between baseline the cardiovascular autonomic neuropathy (CAN) diagnosis (> 1 pathological non-resting test) and levels of test outcomes on liraglutide-induced weight loss was assessed by linear regression models. Results Ninety-nine patients with mean age 48 (SD 12) years, HbA1c 70 (IQR 66;75) mmol/mol and BMI of 30 (SD 3) kg/m2 were assigned to liraglutide (N=50) or placebo (N=49). The CAN diagnosis was not associated with weight loss. A 50% higher baseline level of the 30/15 ratio was associated with a larger weight reduction by liraglutide of -2.65 kg during the trial (95% CI: -4.60;-0.69;, P=0.009). Similar significant associations were found for several HRV indices. Conclusions The overall CAN diagnosis was not associated with liraglutide-induced weight loss in overweight patients with type 1 diabetes. Assessed separately, better outcomes for several CAN measures were associated with higher weight loss, indicating that autonomic involvement in liraglutide-induced weight loss may exist.